2006
DOI: 10.1002/cncr.22325
|View full text |Cite
|
Sign up to set email alerts
|

RIZ1 is epigenetically inactivated by promoter hypermethylation in thyroid carcinoma

Abstract: BACKGROUND. Allelotype studies have suggested that chromosome 1p is frequently lost in thyroid cancers, thus suggesting that there is an important tumor suppressor at this location. RIZ1 (PRDM2), located on 1p36, is a recently described tumor suppressor gene and is a member of the protein methyltransferase superfamily. RIZ1 expression is lost in a variety of tumors, primarily by means of epigenetic mechanisms that involve promoter hypermethylation.METHODS. RIZ1 expression was examined in a panel of thyroid tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 26 publications
1
47
0
Order By: Relevance
“…Epigenetic inactivation by promoter methylation has been implicated as a common mechanism underlying RIZ1 silencing (20,(26)(27)(28)(29)(30). In view of these findings, and our present observation of frequent suppression of RIZ1 mRNA expression we have quantitatively assessed RIZ1 promoter methylation in the tumor panel and four neuroblastoma cell lines.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Epigenetic inactivation by promoter methylation has been implicated as a common mechanism underlying RIZ1 silencing (20,(26)(27)(28)(29)(30). In view of these findings, and our present observation of frequent suppression of RIZ1 mRNA expression we have quantitatively assessed RIZ1 promoter methylation in the tumor panel and four neuroblastoma cell lines.…”
Section: Discussionmentioning
confidence: 85%
“…Somatic RIZ mutations have also been reported, such as frameshift mutations at the C terminus in association with microsatellite instability (21,25), and missense mutations at the N-terminal PR domain in various tumors and cancer cell lines (17). Finally, hypermethylation of promoter P1 has been reported in different types of tumors (20,(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature demonstrates that KAK-1 appears to be morphologically similar to other thyroid carcinoma-derived cell lines such as KAT-4 and KAT-10 [28]. In addition, it seems to have lost expression of several genes, similar to other thyroid carcinoma cell lines [25,[29][30][31]. In this regard, KAK-1 may behave more like a malignant rather than a benign tumor-derived cell line in culture.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of drug treatment was selected based on the growth patterns of this cell line and previous studies from our lab using other thyroid cancer cell lines [25].…”
Section: Drug Treatmentmentioning
confidence: 99%
“…Watson et al11 reported that increased DNA methylation in the HoxA5 promoter region contributed to tumour growth via down‐regulation of HoxA5 expression. Lal et al demonstrated that RIZ1 was epigenetically inactivated by promoter hypermethylation in thyroid carcinoma and identified as a potential novel therapeutic target 12. Thus, aberrant promoter methylation may be an effective way to detect candidate targets for THCA treatment.…”
Section: Introductionmentioning
confidence: 99%